Curriculum Bulletins. - Passow, A. Harry (Educational Leadership, 1957)
The article presents several publications related to the field of education. Like any other Arlington County publications, the guide "Suggestions for Working with the Gifted" results from a long-term effort by staff members who served on Teachers Council on Instruction committee. The publication stresses approaches to teaching but skims over the content for implementing these techniques. The two publications "Guide for Science 9-D Student Development Program" and "Guide for Instruction in Mathematics 9-D Student Development Program" spell out the detailed objectives, content and suggested procedures in the areas of mathematics and science for pupils in the program. "A Guide for Physical Education in the Elementary School" is an inclusive guide for classroom teachers and school administrators concerned with the development of more effective physical education program. The bulletin "Health Teaching in Elementary Schools" presents a course of study prepared to help elementary school pupils absorb information and habits necessary for healthful living.